2021
DOI: 10.3389/fmed.2021.769132
|View full text |Cite
|
Sign up to set email alerts
|

Improved Dry Eye Symptoms and Signs of Patients With Meibomian Gland Dysfunction by a Dietary Supplement

Abstract: Purpose: To explore the therapeutic effect of a dietary supplement on dry eye with meibomian gland dysfunction (MGD).Methods: Sixty patients with MGD-related dry eye were included in this prospective and randomized, placebo-controlled study. All the subjects were treated with eye hot compress, artificial tears, and antibiotic ointment. After that, the patients received dietary supplementary or placebo daily for 12 weeks. The dry eye signs, function of MG, and visual quality of the patients were assessed at 4, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…A cross-sectional study of postmenopausal women (n = 322) found that high dietary intake of omega-3 fatty acids appeared to be protective against MGD [93]. In patients with MGD, several small randomized controlled trials have demonstrated significantly greater improvements with oral omega-3 supplementation versus control treatment in at least some of the signs and symptoms assessed, although findings were inconsistent across studies [94][95][96][97][98]. Larger controlled trials are needed to further evaluate the potential benefits of omega-3 fatty acid supplementation in the management of MGD specifically.…”
Section: Essential Fatty Acidsmentioning
confidence: 99%
“…A cross-sectional study of postmenopausal women (n = 322) found that high dietary intake of omega-3 fatty acids appeared to be protective against MGD [93]. In patients with MGD, several small randomized controlled trials have demonstrated significantly greater improvements with oral omega-3 supplementation versus control treatment in at least some of the signs and symptoms assessed, although findings were inconsistent across studies [94][95][96][97][98]. Larger controlled trials are needed to further evaluate the potential benefits of omega-3 fatty acid supplementation in the management of MGD specifically.…”
Section: Essential Fatty Acidsmentioning
confidence: 99%
“…More accurate parameters that re ect objective visual quality are MTF cutoff and SR [9], which were measured using the Optical Quality Analysis System in our study. The MTF cutoff unit is c/deg, which can indirectly re ect the objective vision of human retinal imaging.…”
Section: Visual Qualitymentioning
confidence: 99%
“…However, due to the complex etiology of dry eye and the characteristics of chronic diseases, resulting in high frequency of drug use, damage to the ocular surface microenvironment [8], increased healthcare costs, poor patient compliance and psychological pressure, often the treatment effect is not ideal. In addition, Meibomian gland (MG) massage, as an important physical therapy, has been reported to easily cause MG or corneal damage, and more serious secondary infections [9]. Therefore, it is very important to nd a new treatment that is economical, simple, safe and effective.…”
Section: Introductionmentioning
confidence: 99%
“…Dry eye disease (DED) is characterized by unstable tear film causing a variety of symptoms and/or visual impairment, affecting 21% to 30% of the population in China and 5% to 50% globally . Meibomian glands are the sole natural source for the lipid layer of the tear film, and their impairment can result in excessive tear evaporation . Meibomian gland dysfunction (MGD) is a chronic, diffuse abnormality and leads to alteration of the tear film, decreased tear film stability, and eye irritation.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8] Meibomian glands are the sole natural source for the lipid layer of the tear film, and their impairment can result in excessive tear evaporation. [9][10][11][12][13] Meibomian gland dysfunction (MGD) is a chronic, diffuse abnormality and leads to alteration of the tear film, decreased tear film stability, and eye irritation. The prevalence of MGD among Asian patients with DED ranges from 46.2% to 69.3%.…”
mentioning
confidence: 99%